1991
DOI: 10.2527/1991.6931074x
|View full text |Cite
|
Sign up to set email alerts
|

Hypertrophy and hyperplasia of bovine fetal tissues during development: fetal liver insulin-like growth factor I mRNA expression.

Abstract: Tissue growth of crossbred fetal beef calves was examined by measuring RNA, DNA, and protein concentrations in liver, heart, and biceps femoris. Furthermore, liver insulin-like growth factor I (IGF-I) mRNA expression and mRNA species size during fetal development was observed. Tissue samples were collected from six fetuses every 42 d of gestation, from d 106 to d 274. In the liver, protein and DNA concentrations decreased, whereas RNA levels remained constant throughout fetal growth. The RNA/DNA and protein/DN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
3
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 0 publications
3
3
0
Order By: Relevance
“…Results from the present study using Northern blotting and hybridization demonstrated that the human IGF-I cDNA used binds to mRNA of adult bovine liver and granulosa cells; transcripts of approximately 7 to 8 kb, 4 kb, 2 kb, and 1 kb were found in liver tissue and granulosa cells. Similar-sized transcripts have been identified in adult bovine (Godfredson et al, 1991;Hannon et al, 1991) and human (Rotwein, 1986) liver and in adult bovine endometrium . Moreover, IGF-I mRNA has been detected in human granulosa cells (Voutilainen and Miller, 1987) and rat ovaries Oliver et al, 1989).…”
Section: Discussionsupporting
confidence: 60%
“…Results from the present study using Northern blotting and hybridization demonstrated that the human IGF-I cDNA used binds to mRNA of adult bovine liver and granulosa cells; transcripts of approximately 7 to 8 kb, 4 kb, 2 kb, and 1 kb were found in liver tissue and granulosa cells. Similar-sized transcripts have been identified in adult bovine (Godfredson et al, 1991;Hannon et al, 1991) and human (Rotwein, 1986) liver and in adult bovine endometrium . Moreover, IGF-I mRNA has been detected in human granulosa cells (Voutilainen and Miller, 1987) and rat ovaries Oliver et al, 1989).…”
Section: Discussionsupporting
confidence: 60%
“…For liver and heart growth, Godfredson et al (1991) showed an accelerated growth in cattle fetus in the third stage of gestation, which agrees with our results. These findings for cattle were also similar to other livestock animals such as pig and sheep.…”
Section: Organ Developmentsupporting
confidence: 93%
“…Fetal body weight (BW) and its components, protein and fat, increase exponentially with gestational age in cattle (Prior and Laster, 1979;Robelin et al, 1991). Different growth patterns for BW, organs, muscles, and body fat, expressed relative to BW in cattle, were reported by Ferrel (1991) and Godfredson et al (1991) and in sheep by Osgerby et al (2002).…”
Section: Introductionmentioning
confidence: 80%
“…The liver is the primary source of circulating IGF (Sjögren et al, 1999), and it is possible that size or development of the liver, as infl uenced by maternal nutrition, could infl uence the expression of components of the IGF system. Absolute, but not relative, fetal liver weight was decreased in fetuses of ewes overnourished during gestation (Wallace et al, 2000(Wallace et al, , 2002Matsuzaki et al, 2004); however, Godfredson et al (1991) reported that abundance of IGF1 mRNA in bovine fetal livers were not correlated with liver weight. Rhoads et al (2000) reported that hepatic expression of the IGF1 gene was reduced in growth-retarded fetuses at 130 d of gestation, reduced in lambs maintained on a low versus high level of nutrition in early postnatal life, but not altered by postnatal nutrition in weaned lambs.…”
Section: Liver Mrna Analysismentioning
confidence: 87%